Characterization of β-Ga2O3 homoepitaxial films and MOSFETs grown by MOCVD at high growth rates. (28th October 2020) - Tadjer, Marko J; Alema, Fikadu; Osinsky, Andrei; Mastro, Michael A; Nepal, Neeraj; Woodward, Jeffrey M; Myers-Ward, Rachael L; Glaser, Evan R; Freitas, Jaime A; Jacobs, Alan G; Gallagher, James C; Mock, Alyssa L; et al.
Abstract: The ultra-wide bandgap semiconductor gallium oxide (Ga2 O3 ) offers substantial promise to significantly advance power electronic devices as a result of its high breakdown electric field and maturing substrate technology. A key remaining challenge is the ability to grow electronic-grade epitaxial layers at rates consistent with 20–40 μ m thick drift regions needed for 20 kV and above technologies. This work reports on extensive characterization of epitaxial layers grown in a novel metalorganic chemical vapor deposition tool that permits growth rates of 1.0–4.0 μ m h −1 . Specifically, optical, structural and electrical properties of epilayers grown at ∼1 μ m h −1 are reported, including employment in an operating MOSFET. The films demonstrate relatively smooth surfaces with a high degree of structural order, limited point defectivity (Nd − Na ≍ 5 × 10 15 cm −3 ) and an optical bandgap of 4.50 eV. Further, when employed in a MOSFET test structure with an n + doped channel, a record high mobility for a transistor structure with a doped channel of 170 cm 2 V −1 s −1 was measured via the Hall technique at room temperature. This work reports for the first time a β-Ga2 O3 MOSFET grown using Agnitron Technology's high growth rate MOCVD homoepitaxial process. These results clearly establish a significant improvement in epilayer quality at growth rates that can support future high voltage power device technologies.